2008
DOI: 10.1016/j.apergo.2008.02.019
|View full text |Cite
|
Sign up to set email alerts
|

What aspects of shiftwork influence off-shift well-being of healthcare workers?

Abstract: Characteristics of shiftwork schedules have implications for off-shift well-being. We examined the extent to which several shift characteristics (e.g., shift length, working Sundays) are associated with three aspects of off-shift well-being: work-to-family conflict, physical well-being, and mental wellbeing. We also investigated whether these relationships differed in four nations. The Survey of Work and Time was completed by 906 healthcare professionals located in Australia, Brazil, Croatia, and the USA. Hier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 24 publications
1
48
0
6
Order By: Relevance
“…Shift-work can impact on the three following aspects: the conflict between work-to-family and social life, physical well-being, and mental well-being (Barnes-Farrell et al, 2008;McVicar, 2003;Tepas et al, 2004). These aspects are particularly emphasized in cases of night shift-work (Tepas et al, 2004), with a reported higher health risk, as it produces symptoms that correspond closely to those of mild or moderate distress (McVicar, 2003).…”
Section: Interpreting the Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shift-work can impact on the three following aspects: the conflict between work-to-family and social life, physical well-being, and mental well-being (Barnes-Farrell et al, 2008;McVicar, 2003;Tepas et al, 2004). These aspects are particularly emphasized in cases of night shift-work (Tepas et al, 2004), with a reported higher health risk, as it produces symptoms that correspond closely to those of mild or moderate distress (McVicar, 2003).…”
Section: Interpreting the Findingsmentioning
confidence: 99%
“…Yildirim & D. Yildirim, 2007) highlighted the relevance of mobbing, conflicts, lack of rewards and recognition by superiors, work demands, work duration, difficulty in balancing work and family commitments, and work context factors. Other authors examined particularly interesting aspects, such as bureaucratic environments (Coates & Howe, 2015;Salmond & Ropis, 2005), the discrepancy between ideal and real work (Coates & Howe, 2015), risk of hazard and injuries related to workers' safety (Markwell & Wainer, 2009) and shift-work (Barnes-Farrell et al, 2008;McVicar, 2003;Tepas et al, 2004). Coates and Howe (2015), in terms of bureaucratic aspects, explained that instances in which staff report administrative issues as their primary concern reflect a contrasting nature of the work; this may conflict with the nurses' professional status while experiencing bureaucratic paperwork or other tasks as activities with which to recover emotional energies when they are feeling the strain of emotional labour.…”
Section: Interpreting the Findingsmentioning
confidence: 99%
“…As such, it would be fair to assume that issues in work scheduling are in fact mismatches in control as described by Maslach et al (2001) and are an antecedent of burnout, especially with regards to professional efficacy. Finally, research evidence also suggests that those employees who work non-standard hours tend to have a poorer experience of work life balance (Barnes-Farrell et al, 2008;Tausig & Fen wick, 2001). Overall, we can expect that the days midwives are not on-call to be less stressful and less intrusive to midwives' experience of work-life balance than the days midwives are on-call.…”
Section: ) Careermentioning
confidence: 99%
“…Exposure to workplace stressors may also have a significant impact on one's experience of work-life balance (e.g., Barnes-Farrell et al, 2008;Johansson, 2002).…”
Section: Stress and Bumout V List Of Tablesmentioning
confidence: 99%
“…SWAT-Healthcare is a modifi cation of a previous international collaborative survey (Barnes-Farrell & Rumery, 2000;BarnesFarrell et al, 2002;Barnes-Farrell et al, 2008;Tepas & Barnes-Farrell, 1997). The survey included the measures of worker's satisfaction with the opportunity to carry out a variety of off-the-job activities, self ratings of different aspects of work demands, workers' ability, health, performan ce and job satisfaction.…”
Section: Procedures and Measuresmentioning
confidence: 99%